The Influence of Load Imposed by the Backpack School in Children and Teens in Brazil - de Paula, A. J F [UNESP]; Silva, J. C P [UNESP]; Silva, J. C R P [UNESP] (Elsevier, 2015)
The scientific community acknowledges that the load carried in backpacks by elementary and middle school students is a critical point and a risk factor for the onset of back pain in children and adolescents, and that this symptom can last in the adulthood. There is a discussion about which is the load that represents less risk, 10% versus 15% of body weight. This cross sectional study aimed to evaluate the load carried by students in primary and secondary state schools, in Brazil and quantifies the percentage established between backpack weight and body mass of these young people carry every day. For data analysis were used descriptive statistics methods and inferential statistics methods such as t-Student test, analysis of variance (ANOVA) and Tukey-test for multiple comparisons. A significance level of 0.05 was considered. Participated in this study 916 students of both genders. The age varies from 10 - 19 years old and mean age of 14,12 (± 2,11 SD). 59,06% carrying bag over 10% of body mass, with the load ranging from 10, 02 to 33,43% (average 13,84 ± 3,48 SD). It was observed that younger students, female and those who opted for the backpack model designed dorsal attachment tended to carry a load higher than 10% of his body weight. 24,45% students complain of back pain and shoulder. Data confirm the use of a cutoff of 10% of body weight for the safe use of backpacks for all school levels. It was concluded that the load carried by the study population is inadequate from the point of view of biomechanics and ergonomics, especially for younger individuals and females, since they are in growth phase, and that the overhead exposes them to greater risk of spinal injuries, with consequent repercussions in adulthood.
Keywords: Back pain; Design; Ergonomics; School backpack; Student